Cognitive Function Does Not Impact Self-reported Health-Related Quality of Life in Heart Failure Patients. Issue 5 (September 2016) - Gathright, Emily C.; Fulcher, Michael J.; Dolansky, Mary A.; Gunstad, John; Redle, Joseph D.; Josephson, Richard; Moore, Shirley M.; Hughes, Joel W.
Abstract : Background: Adults with heart failure (HF) often demonstrate impairment across multiple domains of cognitive functioning and report poor health-related quality of life (HRQoL). Previous researchers have found that cognitive deficits were generally not associated with HRQoL in a carefully evaluated sample. The exception was memory, which was only weakly associated with HRQoL. However, cognitive deficits interfere with self-care and disease self-management, which could be expected to affect HRQoL. Objective: We sought to verify this counterintuitive finding in a large well-characterized sample of HF patients using a well-validated neuropsychological battery. Methods: Participants were 302 adults (63% male) predominately white (72.5%) HF patients (68.7 ± 9.6 years) recruited from 2 medical centers. Self-reported HRQoL was assessed using the Kansas City Cardiomyopathy Questionnaire. Participants completed a neuropsychological battery examining attention, executive function, memory, and visuospatial functioning. Hierarchical multiple linear regression was used for analyses. Results: Mild global cognitive impairment was observed in 29.5% of the sample (Modified Mini-Mental State [3MS] Examination score <90). Controlling for gender, depression, HF severity, premorbid IQ, comorbidities, and education, only executive function predicted HRQoL, β = .17, P < .05. However, executive function accounted for only 0.6% of the variance in HRQoL. Conclusion: Cognitive function generally did not predict HRQoL in HF patients. The correlates of HRQoL in HF do not appear to include mild cognitive impairment. Other factors may play a bigger role such as disease severity, age, and depressive symptoms. Future studies should investigate modifiable determinants of HRQoL in HF patients, toward the goal of finding interventions that preserve HRQoL during this chronic illness.